La instalación en Europa del sistema antimisiles de Estados Unidos - Lara Fernández, Belén (UNISCI Discussion Papers, 2007)
Bush’s purpose of deploying his strategic defensive system in European soil has pushed many questions into the debate: how it is affecting and will affect relations between the U.S., Russia and European Union; the deployment of interceptors in Poland to face an Iranian attack; the possibility of a new arms race; the destruction of the arms control treaties; and the consequences for the pacific use of the outer space.